Single Amino Acid Substitution in Homogentisate Dioxygenase Affects Melanin Production in Bacillus thuringiensis - Yang, Wenjun; Ruan, Lifang; Tao, Jiangming; Peng, Donghai; Zheng, Jinshui; Sun, Ming (Frontiers in Microbiology, 2018)
Bacillus thuringiensis formulation losing its activity under field conditions due to UV radiation and photoprotection of B. thuringiensis based on melanin has attracted the attention of researchers for many years. Here, a single amino acid substitution (G272E) in homogentisate 1,2-dioxygenase was found to be responsible for pigment overproduction in B. thuringiensis BMB181, a derivative of BMB171. Disrupting the gene encoding homogentisate dioxygenase in BMB171 induced the accumulation of the homogentisic acid and provoked an increased pigment formation. To gain insights into homogentisate 1,2-dioxygenase in B. thuringiensis, we constructed a total of 14 mutations with a single amino acid substitution, and six of the mutant proteins were found to affect the melanin production when substituted by alanine. This study provides a new way to construct pigment-overproducing strains by impairing the homogentisate dioxygenase with a single mutation in B. thuringiensis, and the findings will facilitate a better understanding of this enzyme.